CEO narcissism and its dual impact on Environmental, Social and Governance (ESG) practices and stock market reaction - Grossi, Janaína Cássia (2024)
This dissertation investigates the complex interplay between CEO narcissism and Environmental, Social, and Governance (ESG) practices within corporations, along with the subsequent impact on stock market reactions. Comprising three distinct yet interconnected studies, this research aims to contribute to the understanding of behavioral factors in corporate sustainability and finance. As the ESG agenda gains momentum, it has become a focal point in finance, management, and strategy research. In August 2024, the number of papers indexed in Science Direct on ESG was ten times higher than in 2017. However, estimating causal relationships in ESG research is complex due to endogeneity issues. The first study conducts a systematic review of 117 studies in ESG corporate finance, focusing on those that attempt to establish causal relationships. The review highlights the methodologies used to address endogeneity and provides insights into best practices for future research. The second study examines the impact of CEO narcissism on firms’ performance and ESG disclosure. The sample covers US companies from the S&P 500 Index between 2015 and 2022. The results reveal that firms led by more narcissistic CEOs consistently show higher ESG disclosure scores, with the strongest effect observed in environmental disclosures. These findings suggest that narcissistic CEOs may actively engage in ESG practices to enhance their public image and gain visibility. Furthermore, companies led by highly narcissistic CEOs tend to have fewer reported ESG controversies, suggesting that these leaders may be sensitive to public perceptions and their reputations. To address potential endogeneity concerns, the study applied the Heckman two-step correction method and performed a Propensity Score Matching (PSM) analysis. Both approaches confirmed the robustness of the main results, demonstrating that narcissistic CEOs continue to show a strong positive effect on ESG disclosure, even after controlling for potential selection bias. The third study investigates the impact of ESG-related news on stock prices, focusing on the role of CEO narcissism and ESG news sentiment. Using a sample of S&P 500 companies from 2015 to 2022, the research employs event study methodology and regression analysis to examine how market reactions are shaped by CEO narcissism and the sentiment of ESG news. The findings reveal that firms led by highly narcissistic CEOs experience higher abnormal returns immediately following ESG news releases, suggesting that investors may respond favorably to such leadership in the short term. However, the positive effect of CEO narcissism diminishes when the ESG news sentiment is positive, indicating possible investor skepticism. Conversely, when news sentiment is negative, narcissistic CEOs seem to mitigate the impact, enhancing investor confidence. For firms with less narcissistic CEOs, abnormal returns decline post-ESG news, though positive sentiment can offset this decline. The results highlight the significance of leadership traits in influencing corporate strategies and market responses to ESG disclosures.